Ambipolar organic field-effect transistors based on diketopyrrolopyrrole derivatives containing different π-conjugating spacers. Issue 20 (18th April 2016) - Lin, Gaobo; Qin, Yunke; Zhang, Jiajia; Guan, Ying-Shi; Xu, Hai; Xu, Wei; Zhu, Daoben
Abstract : We report the synthesis and characterization of two ambipolar diketopyrrolopyrrole derivatives containing different π-conjugating spacers. Abstract : We report the synthesis and characterization of two new DPP-based small molecules, BTDPPCN and TTDPPCN. By variation of π-conjugating spacers from bithiophene to thieno[3, 2- b ]thiophene, a lower LUMO level is obtained for TTDPPCN, but both compounds have a similar band gap of about 1.6 eV. Under ambient conditions, the excellent ambipolarity of BTDPPCN is demonstrated by balanced charge carrier mobilities of 0.065 and 0.031 cm 2 V −1 s −1 for n- and p-channels after thermal annealing. The FETs based on TTDPPCN films also showed ambipolar charge transport properties with a very high electron mobility of 0.80 cm 2 V −1 s −1 upon thermal annealing at 90 °C and a hole mobility of 0.024 cm 2 V −1 s −1 at 150 °C.